2014
DOI: 10.1017/s1368980014001499
|View full text |Cite
|
Sign up to set email alerts
|

Associations between socio-economic status and school-day dietary intake in a sample of grade 5–8 students in Vancouver, Canada

Abstract: Objective: To examine associations between students' socio-economic status (SES) and school-day dietary intake, and the roles of parents and peers in shaping these associations. Design: A cross-sectional survey measured school-day intake of vegetables, whole grains, low-fat milk, packaged snack foods and sugar-sweetened beverages. Logistic regression models examined associations between SES (parental education and food insecurity status) and dietary outcomes during or en route to or from school, and examined w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
31
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 36 publications
(33 citation statements)
references
References 40 publications
(56 reference statements)
2
31
0
Order By: Relevance
“…The search output provided 8,464 studies for eligibility review after removal of duplicates, of which 8,417 studies were excluded upon review of titles and abstracts. From 47 studies eligible for the full‐text review process, 27 studies were excluded, yielding an eligible 20 studies for the final review (Figure ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The search output provided 8,464 studies for eligibility review after removal of duplicates, of which 8,417 studies were excluded upon review of titles and abstracts. From 47 studies eligible for the full‐text review process, 27 studies were excluded, yielding an eligible 20 studies for the final review (Figure ).…”
Section: Resultsmentioning
confidence: 99%
“…The dietary behaviours included and the number of studies assessing them were: Fruit and Vegetable intake (FV)( n = 10), sugar‐sweetened beverage and soft drink consumption (SSB/SDC)( n = 9) 44,46,48,49,55,58,59,61,62, breakfast consumption ( n = 3), and energy‐dense snack/fast food consumption(n = 3) …”
Section: Resultsmentioning
confidence: 99%
“…In the United Kingdom, 1 study examining dietary contributions of nutrients from lunch among older adolescents reported relatively lower intakes of vitamin C, folate, calcium, and iron compared with the mean caloric contribution (Prynne et al 2013). In Canada, a limited number of studies from regional, context-specific samples have examined in-school dietary intakes suggesting overall poor dietary practices (Woodruff et al 2010;Taylor et al 2012;Ahmadi et al 2015;Neilson et al 2017), but no study has assessed the dietary contributions from foods eaten at school in relation to whole-day intakes or compared nutrient intake patterns between school and non-school hours.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, adolescents living in food-insecure households are more likely to report poorer quality diets (Kirkpatrick and Tarasuk 2008). However, Canadian studies drawing from smaller, regional samples report weak associations about the role of SES in shaping dietary outcomes for younger children (Attorp et al 2014;Ahmadi et al 2015). No study has compared in-school dietary outcomes across demographic and socioeconomic characteristics in a large nationally representative sample of Canadian children.…”
Section: Introductionmentioning
confidence: 99%
“…In 2012, the survey was administered to 950 students in grades 5-8 in 20 elementary and six secondary schools. Key findings are reported in three student theses and several peer reviewed papers (Ahmadi, 2013;Ahmadi, Black, Velazquez, Chapman, & Veenstra, 2015;Daepp, 2016;Stephens, 2014;;Stephens, Black, Chapman, Velazquez, & Rojas, 2016;Velazquez, Black, Billette, Ahmadi, & Chapman, 2015). Overall, IEAT findings suggested that in the 2011-2012 school year (reflecting the early years of TEGS), less than half of students reported engaging in most of the food and nutrition activities examined, including: food preparation (36%), choosing/tasting healthy foods (27%), learning about Canada's Food Guide (CFG) (45%), learning about foods grown in BC (35%), gardening (21%), composting (32%), and recycling (51%).…”
Section: Individual Eating Assessment Tool (Ieat)mentioning
confidence: 84%